Environmental factors structuring Arctic megabenthos—a case study from a shelf and two fjords - Meyer, Kirstin S.; Sweetman, Andrew K.; Young, Craig M.; Renaud, Paul E. (Frontiers in Marine Science, 2015)
From photographic samples, we describe the benthic megafaunal communities in two north Svalbard fjords and on the adjacent continental shelf. We analyze the fauna in relation to abiotic factors of depth, bottom water temperature, percent cover of hard substratum, heterogeneity of stone size, and bottom-water turbidity to explore how these factors might affect the fauna and how they are related to the functional traits (size, morphology, mobility, colonial/solitary, and feeding type) of the megabenthos. Depth and bottom water temperature were consistently the strongest correlates with faunal composition and functional traits of the constituent species. A greater proportion of the variability in the functional traits of the megabenthos could be explained by abiotic factors rather than faunal composition, indicating that the abiotic factors of depth and temperature were strongly related to the functional traits of the megabenthos. On a local scale, stone size heterogeneity explained most variation in the functional traits of the megabenthos in one fjord. The results of this case study show a significant relationship between bottom water temperature and the functioning of north Svalbard megabenthic communities. Warming temperatures in the Arctic will likely decrease the variety of functional traits represented in Svalbard megabentos, resulting in scavenger-dominated communities. A reduction in megabenthic biomass may also result, reducing energy availability to higher trophic levels.